Intelligent device to increase water pressure - Hassan, Hanita (Universiti Teknologi Malaysia, 2004)
Low water pressure always happens at the highland area. During peak hours, consumers always have this problem, especially at the end user of the water transmission. With the technology that we have today, this problem can be solved easily. In most cases this problems are solved by using pumps. This project describes a new design of a water pressure increasing device for the use of the end user. The device enables the water pressure to be increased during low water pressure condition. This project also focuses on the water transmission aspects such as the pipe design and size that is used for the water distribution system. This project uses a basic vacuum concept in science; creating a low water pressure area which will suck the water. An air compressor is used in this project to give a force to push the water in order to increase the water flow. As to connect between the pipeline transmission and the air compressor, the designs of the Y junction pipe involved. The Y junction pipe is designed with variable diameter of pipe size to see the effect in flow rate and pressure of the water. Flow meter and pressure gauge were been deployed in this project to measure the value of the flow rate and pressure of the water as the Y junction pipe is connected to the water pipeline. All the measured values will be placed in a database system to give users full access to use it and to interact with the measured data.